The in Vitro Effects of Echinophora Cinerea on Cell Line, Giardia Lamblia Cyst, and Giardia Muris - Behrouz Ezatpour; Mahmoud Bahmani *; Mehdi Azami; Farnaz Kheirandish *; Mahmoud Rafieian-Kopaei * (Lorestan University of Medical Sciences, 2018)
Background and Aim: Currently, Giardia lamblia is the most common parasitic protozoan in many countries, including Iran, and the most important cause of diarrhea among travelers, children, and homosexuals. Chemical drugs could be used to treat giardiasis. These drugs can have carcinogenic effects and can lead to drug resistance, which is being reported from different regions across the world, including Iran. Materials and Methods: The present study was conducted to phytochemically analyze Echinophora cinerea, and to compare the in vitro effects of E. cinerea extract and metronidazole on G. lamblia and Giardia muris. In addition, this research investigates the in vitro effect of ethanolic E. cinerea extract on G. lamblia and G. muris cysts as well as the cytotoxicity of this extract on cell line from the SFIF-PI-44 (intestine of sheep) and IEC-18 (ileum of rat). Results: α-phellandrene was found to be the most significant and abundant compound of E. cinerea. According to the findings, 4 and 8 mg/mL of E. cinerea caused the gradual destruction of G. muris cysts (6.83 and 7.89 cysts/h, respectively). Moreover, 4 and 8 mg/mL of the same extract caused the gradual destruction of G. lamblia cysts (7.92 and 7.89 cysts/h, respectively).  Furthermore, the mean rate of cysts destruction was found to be 8.83 cysts/h by 8 mg/mL of E. cinerea extract. Conclusion: Regarding the optimal effects of E. cinerea, further research seems necessary on the in vitro antigiardial effects of this plant.